POLICY STRATEGIES IN HANDLING ROHINGYA REFUGEES IN INDONESIA TO SUPPORT SUSTAINABLE JUSTICE - Sari, Athina Kartika; Zulfikar, Zulfikar; Nurachmad, Much; Muazarah, Kharraz (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Indonesia’s position as a transit country for refugees presents complex challenges in law enforcement, financial stability, social security, and foreign policy. Despite Indonesia’s commitment to refugee protection under Article 27 paragraph (2) of Law No. 37 of 1999 on Foreign Relations and Presidential Regulation No. 125 of 2016 concerning the Handling of Refugees from Abroad, many legal and institutional gaps persist. This study employs a normative juridical method to examine two key questions: (1) the legal status of Rohingya refugees under international and national law, and (2) the legal strategies that Indonesia can adopt to promote sustainable justice in refugee management. The findings reveal that the arrival of Rohingya refugees in Banda Aceh on 14 November 2023 highlights the lack of clear legal recognition, as current procedures do not align with the 1951 Refugee Convention, the 1967 Protocol, or Law No. 9 of 1992 on Immigration. Although legal violations are evident, humanitarian considerations and the non-refoulement principle remain fundamental. To address these challenges, this research proposes strategic policy measures, including strengthening collaboration with local communities and NGOs, promoting economic empowerment through taxation on income-generating refugees, and utilizing third-party donor funding schemes to facilitate refugee relocation to countries that are parties to the Refugee Convention.